Long-term bleeding risk prediction in ‘real world’ patients with atrial fibrillation: Comparison of the HAS-BLED and ABC-Bleeding risk scores - Asunción Esteve-Pastor, María; Miguel Rivera-Caravaca, José; Roldán, Vanessa; Vicente, Vicente; Valdés, Mariano; Marín, Francisco; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2017)
Risk scores in patients with atrial fibrillation (AF) based on clinical factors alone generally have only modest predictive value for predicting high risk patients that sustain events. Biomarkers might be an attractive prognostic tool to improve bleeding risk prediction. The new ABCBleeding score performed better than HAS-BLED score in a clinical trial cohort but has not been externally validated. The aim of this study was to analyze the predictive performance of the ABC-Bleeding score compared to HAS-BLED score in an independent “real-world” anticoagulated AF patients with long-term follow-up. We enrolled 1,120 patients stable on vitamin K antagonist treatment. The HAS-BLED and ABC-Bleeding scores were quantified. Predictive values were compared by c-indexes, IDI, NRI, as well as decision curve analysis (DCA). Median HAS-BLED score was 2 (IQR 2–3) and median ABC-Bleeding was 16.5 (IQR 14.3–18.6). After 6.5 years of follow-up, 207 (2.84%/year) patients had major bleeding events, of which 65 (0.89%/year) had intracranial haemorrhage (ICH) and 85 (1.17%/year) had gastrointestinal bleeding events (GIB). The c-index of HAS-BLED was significantly higher than ABC-Bleeding for major bleeding (0.583 vs 0.518; p=0.025), GIB (0.596 vs 0.519; p=0.017) and for the composite of ICH-GIB (0.593 vs 0.527; p=0.030). NRI showed a significant negative reclassification for major bleeding and for the composite of ICH-GIB with the ABC-Bleeding score compared to HAS-BLED. Using DCAs, the use of HAS-BLED score gave an approximate net benefit of 4% over the ABC-Bleeding score. In conclusion, in the first “real-world” validation of the ABC-Bleeding score, HAS-BLED performed significantly better than the ABC-Bleeding score in predicting major bleeding, GIB and the composite of GIB and ICH.Note: The review process for this manuscript was fully handled by Christian Weber, Editor in Chief.Supplementary Material to this article is available online at www.thrombosis-online.com.